2000
DOI: 10.1128/jb.182.22.6440-6450.2000
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Collagen-Binding S-Layer Protein CbsA of Lactobacillus crispatus

Abstract: The cbsA gene of Lactobacillus crispatus strain JCM 5810, encoding a protein that mediates adhesiveness to collagens, was characterized and expressed in Escherichia coli. The cbsA open reading frame encoded a signal sequence of 30 amino acids and a mature polypeptide of 410 amino acids with typical features of a bacterial S-layer protein. The cbsA gene product was expressed as a His tag fusion protein, purified by affinity chromatography, and shown to bind solubilized as well as immobilized type I and IV colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
146
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(152 citation statements)
references
References 46 publications
(54 reference statements)
5
146
0
1
Order By: Relevance
“…It has been proposed that S-layer plays a role as a protective sheath in Lactobacillus acidophilus ATCC 4356. In addition, some studies identified that the S-layer proteins of Lactobacilli were important for hydrophobicity, autoaggregation and adherence of this bacteria to different host surfaces (Frece et al, 2005;Greene & Klaenhammer, 1994;Hynonen et al, 2002;Kos et al, 2003;Pelletier et al, 1997;Sillanpaa et al, 2000;Toba et al, 1995;Vadillo-Rodriguez et al, 2004Van der Mei et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that S-layer plays a role as a protective sheath in Lactobacillus acidophilus ATCC 4356. In addition, some studies identified that the S-layer proteins of Lactobacilli were important for hydrophobicity, autoaggregation and adherence of this bacteria to different host surfaces (Frece et al, 2005;Greene & Klaenhammer, 1994;Hynonen et al, 2002;Kos et al, 2003;Pelletier et al, 1997;Sillanpaa et al, 2000;Toba et al, 1995;Vadillo-Rodriguez et al, 2004Van der Mei et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It demonstrates 37% similarity to Biofilm Associated Protein (BAP) found in bovine Staphylococcus aureus strains 33 . We further identified four paralogous proteins predicted to mediate autoaggregation and adherence to collagen 34 . They have a central region rich in Ser/Thr/Gln, demonstrate physical properties quite similar to cell surface-layer proteins, and can be further divided into two sets.…”
Section: Heme and Iron Requirementmentioning
confidence: 99%
“…Moreover, the hydrophobicity of the cell surface of the strain Lactobacillus acidophilus ATCC 4356 can be varied in accordance with the change of the ionic strength of the medium [43]. In a sequencing study of the S-layer proteins in Lactobacillus acidophilus, Lactobacillus crispatus and Lactobacillus helveticus a high degree of homology in one third of their Cterminus is demonstrated [36].…”
Section: Microorganisms With Probiotic Propertiesmentioning
confidence: 99%
“…The molecular weight of the S-layer proteins in lactobacilli ranges from 40 kDa to 60 kDa and they are one of the smallest known S-layer proteins [31,36,39,40]. Compared with many other S-layer proteins, which are of acidic nature, those in lactobacilli are characterized by high values of their isoelectrical points [41].…”
Section: Microorganisms With Probiotic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation